A Textbook Oriented Towards Critical Thinking Skills on The IPAS Subject (Energy Crisis) for Primary School - Kartono, Kartono; Auliya Vilda Ghasya, Dyoty; Pranata, Rio; Tesi Muskania, Ricka; Irfan Izudin, Muhammad; Fatmadiwi, Anggi; Mu’afiyah, Rofidatul (Jurnal Ilmiah Teunuleh, 2025)
Critical thinking is not a skill that develops on its own. This ability must be cultivated through activities that encourage individuals to think critically. Schools, as educational institutions, have a responsibility to help students develop critical thinking skills. The purpose of this study is to determine the validity of the developed critical-thinking-oriented textbook on energy crisis threats for IPAS Phase C in primary schools and to describe teacher and student responses regarding the practicality of this textbook. The research method used is Research and Development (R&D) with both quantitative and qualitative analysis. Data collection instruments included questionnaires, checklists, and interview guidelines. The study resulted in the development of a critical-thinking-oriented textbook on energy crisis threats for IPAS Phase C. The material validation score was 90.62, categorized as highly valid; the language validation score was 85, also highly valid; and the design validation score was 90, categorized as highly valid. Furthermore, the practicality response questionnaires yielded scores of 93.57 from students and 95.14 from teachers, both categorized as highly practical.